Pengaruhfaktor Keperilakuan Organisasi Terhadap Sistem Akuntansi Keuangan Daerahdi Kabupaten GroboganJawa Tengah - Solichin, Ahmad Nur, Drs. Suyatmin Waskito Adi, M.Si (2016)
The purpose of this study was to analyze the influene of the organazational behavior (support,traning and clarity of purpose) against the financial accounting system uses the area in Grobogan,Central Java. This type of research is quantitative survey research methods. The population in this research is the entire SEGWAY ManajerGrobogan, Central Java.The sample in this research was taken with purposive sampling method sampling in accordance with predetermined criteria. The number of samples collected 50. Analytical tools which inuse is multiple regression which includes test validity and reliability test, a test ofnormality,testmultikolinieritas, heteroskedastitas test, multyple linear regression test, f test, test the determination of the coefficient R^2 and t test The results showed that organizational behavior (support, training, the clarity of purpose) effect on the usability of financial accounting area it shows the support supervisor, clarity of purpose and training may affect the usefulness of the financial accounting systems of the region. Keywords: organizational behavior, support, training, system of goal clarity financial accounting areas.